DNA methylation patterns of adult survivors of adolescent/young adult Hodgkin lymphoma compared to their unaffected monozygotic twin. Issue 6 (12th May 2019) - Wang, Jun; Van Den Berg, David; Hwang, Amie E.; Weisenberger, Daniel; Triche, Timothy; Nathwani, Bharat N.; Conti, David V.; Siegmund, Kim; Mack, Thomas M.; Horvath, Steve; Cozen, Wendy
Abstract: DNA methylation (DNAm) silences gene expression and may play a role in immune dysregulation that is characteristic of adolescent/young adult Hodgkin lymphoma (AYAHL). We used the Infinium HumanMethylation27 BeadChip to quantify DNAm in blood ( N = 9 pairs, mean age 57.4 y) or saliva ( N = 36 pairs, mean age 50.0 y) from long-term AYAHL survivors and their unaffected co-twins. Epigenetic aging (DNAm age) was calculated using previously described methods and compared between survivors and co-twins using paired t-tests and analyses were stratified by sample type, histology, sex, age at sample collection and time since diagnosis. Differences in blood DNAm age were observed between survivors and unaffected co-twins (64.1 vs. 61.3 years, respectively, p = .04), especially in females ( p = .01); no differences in saliva DNAm age were observed. Survivors and co-twins had 74 (in blood DNA) and 6 (in saliva DNA) differentially methylated loci. Our results suggest persistent epigenetic aging in AYAHL survivors long after HL cure.